Academic Health Centers and Humanitarian Crises: One Health System's Response to Unaccompanied Children at the Border. (17th February 2023) - Devaskar, Sherin U.; Cunningham, Coleen K.; Steinhorn, Robin H.; Haq, Cynthia; Spisso, Johnese; Dunne, William; Gutierrez, Juan Raul; Kivlahan, Coleen; Bholat, Michelle; Barakat, Suzanne; de Leon Siantz, Mary Lou; Romero, Stephanie; et al.
Abstract : University of California Health (UCH) provided a system-wide, rapid response to the humanitarian crisis of unaccompanied children crossing the southern U.S. border in the midst of the COVID-19 pandemic in 2021. In collaboration with multiple federal, state, and local agencies, UCH mobilized a multidisciplinary team to deliver acute general and specialty pediatric care to unaccompanied children at 2 Californian emergency intake sites (EISs). The response, which did not disrupt normal UCH operations, mobilized the capacities of the system and resulted in a safe and developmentally appropriate environment that supported the physical and mental health of migrant children during this traumatic period. The capacities of UCH's 6 academic health centers ensured access to trauma-informed medical care and culturally sensitive psychological and social support. Child life professionals provided access to exercise, play, and entertainment. Overall, 260 physicians, 42 residents and fellows, 4 nurse practitioners participated as treating clinicians and were supported by hundreds of staff across the 2 EISs. Over 5 months and across both EISs, a total of 4, 911 children aged 3 to 17 years were cared for. A total of 782 children had COVID-19, most infected before arrival. Most children (3, 931) were reunified with family or sponsors. Continuity of care after reunification or placement in a long-term shelter was enhanced by use of an electronic health record. The effort provided an educational experience for residents and fellows with instruction in immigrant health and trauma-informed care. The effort benefitted from UCH's recent experience of providing a system-wide response to the COVID-19 pandemic. Lessons learned are reported to encourage the alignment and integration of academic health centers' capacities with federal, state, and local plans to better prepare for and respond to the accelerating need to care for those in the wake of disasters and humanitarian crises.